1989
DOI: 10.1111/j.1570-7458.1989.tb02306.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining the functional response of the parasitoid Venturia canescens

Abstract: A series of experiments were undertaken to determine the factors responsible for the maximum number of hosts attacked by the parasitoid Venturia canescens (Gravenhorst) (Hymenoptera:Ichneumonidae) in the course of functional response experiments. Egg limitation is not a constraint on the maximum number of parasitoid progeny produced per day. Rather, the constraints arise from the requirement that eggs must be moved from the ovarioles to the oviducts and the rate at which this occurs, together with the existenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…6, ANOVA, during the day with a "remaining" (r = 0.77, search (r = 0.73, P < 0.001). No change decreasing egg load P < 0.001) P < 0.001) in their walking speed (r = 0.55, P < 0.001 and see was found (a = 0.05) their Table 6 Pak et al 1985Collins and Dixon 1986Collins and Dixon 1986Trudeau and Gordon 1989 a No statistical effect of age on searching activity was found. Initial egg load was estimated as a function of the egg load determined at the end of an observation and size, i.e.…”
Section: Theorymentioning
confidence: 82%
“…6, ANOVA, during the day with a "remaining" (r = 0.77, search (r = 0.73, P < 0.001). No change decreasing egg load P < 0.001) P < 0.001) in their walking speed (r = 0.55, P < 0.001 and see was found (a = 0.05) their Table 6 Pak et al 1985Collins and Dixon 1986Collins and Dixon 1986Trudeau and Gordon 1989 a No statistical effect of age on searching activity was found. Initial egg load was estimated as a function of the egg load determined at the end of an observation and size, i.e.…”
Section: Theorymentioning
confidence: 82%
“…V. canescens females emerge with mature and immature eggs (Trudeau and Gordon 1989;Harvey et al 2001;Roberts and Schmidt 2004) that mature during the adult lifetime (synovigeny). With continuous sugar access, thelytokous V. canescens can produce up to several 100 eggs over their lifetime (Harvey et al 2001;Roberts and Schmidt 2004).…”
Section: Biological Materials and Culturesmentioning
confidence: 98%
“…Experiments have shown that following host encounters, RM-wasps lay fewer eggs initially and more eggs later compared to RP-wasps (Beck et al, 2001). The observed differences in egg deposition strategies may be because of a lower egg load in RM-wasps (Beck et al, 1999), which correlates with lower egg deposition rates (Trudeau and Gordon, 1989).…”
Section: Introductionmentioning
confidence: 99%